IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS MELALUI PROGRAM PENANAMAN BIBIT BUAH: ACT FOR EARTH: GLOBAL HANDS, SUSTAINABLE IMPACT - Aryani, Dwi Nita; Soeparto; Paramita, Niken; Liskinasih, Ayu; Pudyastuti, Zusana Eko; Tarra, Mustika; Suhartatik; Dewi, Sulih Indra; Widodo, Teguh; Ramadhan, Muhammad Mahesa; Aini, Fica Aida Nadhifatul; Efendi , Erfan (Yayasan Baitul Hikmah al-Zain, 2025)
Climate change and environmental degradation are global challenges, the condition of the world's ecosystem is starting to change, the damaged environment, unpredictable climate and weather, affecting the sustainability of life of living things. Sustainable Development Goals (SDGs) are designed to address various global challenges, including climate change and environmental degradation. The purpose of this community service activity (PKM) is to increase public awareness of the importance of protecting the environment, greening critical land, increasing local food security, improving the community economy, empowering communities, increasing inter-institutional collaboration, realizing sustainable development, introducing PKM activities, building global-local collaboration. This service was carried out in Sitiarjo Village, Sumbermanjing Wetan District, Malang Regency. 200 fruit seedlings are assistance from the Public Company (Perum) Jasa Tirta 1 Malang. The planting of these fruit seedlings was initiated by a consortium of the International Affairs Office (KUI) throughout Malang Raya, and was carried out in February 2025. The participants involved were 140 people consisting of foreign and local students, lecturers, KUI staff, junior high and high school students and the Sitiarjo village youth organization. In addition, material was also provided on Let's Garden Agroforestry Model, how to fertilize and farm in Japan. The PKM activity has been carried out well and received a positive response from the community. This PKM has a positive impact on environmental goodness, increasing community and village income, and world sustainability.